WORKING POSTURE ANALYSIS AND DESIGN USING RULA (RAPID UPPER LIMB ASSESSMENT) METHOD IN PRODUCTION PROCESS AT PT. INDANA PAINT - Yongky Kusnandar Djiono; Sunday Noya (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2013)
Working posture can affect the comfort and productivity of labor in doing manual work. In this study, RULA method is used to determine the risk level of musculoskeletal disorders (MSDs) injury in the production process at PT. Indana Paint (consists of mixing and packaging steps for water-based paint, solvent-based paint, and base paint production), and then given proposed improvements to reduce the risk level. Method used in this research is direct observation and video recording of every work element to determine some awkward postures that will be assessed using RULA method. Thirty awkward postures are found, there are 7 working posture (23.3%) have low risk level, 11 working posture (36.7%) have medium risk level, and 12 working posture (40%) have high risk level. Proposed improvements given is to brief the workers on appropriate lifting technique and working methods, adding mechanical aids for handling drums, and working position height adjustment.